1983
DOI: 10.1161/01.hyp.5.2_pt_2.i155
|View full text |Cite
|
Sign up to set email alerts
|

Neural contribution to renal hypertension following acute renal artery stenosis in conscious rats.

Abstract: SUMMARY To assess the hemodynamic changes during acute renal artery stenosis (RSt) and their dependence on alterations in the renin-angiotensin and sympathetic nervous systems, we studied conscious rats chronically instrumented with miniaturized pulsed-Doppler flow probes. Probes were implanted on the superior mesenteric and both renal arteries, and on the lower abdominal aorta for measurement of mesenteric (MR), renal (RR), and hindquarters (HQR) vascular resistance. Unilateral RSt, with a pneumatic cuff occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1983
1983
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…33 Of note, these effects are long lasting and do not occur with infusion of vehicle. 34 In conjunction with the demonstration of elevated sympathetic activity in experimental renal artery stenosis 35 Figure 1. Causes and consequences of sympathetic activation in CRF: Several forms of "renal injury" seem to have the ability to stimulate afferent signaling via sensory renal nerves.…”
Section: Renal Injury and Ischemiamentioning
confidence: 94%
“…33 Of note, these effects are long lasting and do not occur with infusion of vehicle. 34 In conjunction with the demonstration of elevated sympathetic activity in experimental renal artery stenosis 35 Figure 1. Causes and consequences of sympathetic activation in CRF: Several forms of "renal injury" seem to have the ability to stimulate afferent signaling via sensory renal nerves.…”
Section: Renal Injury and Ischemiamentioning
confidence: 94%
“…The autonomic nervous system could have been involved in the chronic responses to stenosis in at least two main ways: by its activity being modulated by Ang II either peripherally or centrally (See References [41][42][43] or by afferent neural input from the stenotic kidney. 6 -8 However, the results of the present study in conscious recumbent dogs did not reveal a significant role for the autonomic nervous system in the hemodynamic responses.…”
Section: Role Ofautonomic Nervous Systemmentioning
confidence: 99%
“…Previous studies have suggested that sympathetic outflow may participate in the development of hypertension in rats following reduced renal perfusion pressure 24 and in dogs during intrarenal infusion of adenosine 9 or norepinephrine. 25 The present data indicate that, at least in the DS, elevation of sodium intake by an 8% sodium chloride diet does not activate renal afferent neural pathways leading to elevation of arterial pressure.…”
Section: Renal Nerves and Hypertension In Dsiosborn Et Almentioning
confidence: 99%